2017
DOI: 10.1186/s12885-017-3169-9
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of TWIST1-RELA binding by mutation and competitive inhibition to validate the TWIST1 WR domain as a therapeutic target

Abstract: BackgroundMost cancer deaths result from tumor cells that have metastasized beyond their tissue of origin, or have developed drug resistance. Across many cancer types, patients with advanced stage disease would benefit from a novel therapy preventing or reversing these changes. To this end, we have investigated the unique WR domain of the transcription factor TWIST1, which has been shown to play a role in driving metastasis and drug resistance.MethodsIn this study, we identified evolutionarily well-conserved r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…Moreover, MSN-HA-siQ control mice developed great amounts of tumor, metastasis, and ascites as compared to MSN-HA-siTWIST + cisplatin group (Figure 5 A-C) which showed no large dispersed lesions. It is important to note that cisplatin + MSN-siTWIST hindered cancer growth by almost 50%, cumulatively, (Figure 5, A-C), as shown previously 32 . However, MSN-HA-siTWIST + cisplatin combination therapy inhibited tumor growth to an even more significant degree, with almost a 75% drop in number of tumor in comparison to CISPLATIN alone and 90% compared to controls (Figure 5, A-C).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, MSN-HA-siQ control mice developed great amounts of tumor, metastasis, and ascites as compared to MSN-HA-siTWIST + cisplatin group (Figure 5 A-C) which showed no large dispersed lesions. It is important to note that cisplatin + MSN-siTWIST hindered cancer growth by almost 50%, cumulatively, (Figure 5, A-C), as shown previously 32 . However, MSN-HA-siTWIST + cisplatin combination therapy inhibited tumor growth to an even more significant degree, with almost a 75% drop in number of tumor in comparison to CISPLATIN alone and 90% compared to controls (Figure 5, A-C).…”
Section: Resultssupporting
confidence: 83%
“…The chemotherapy only treatment mouse group (CISPLATIN only) was left with 60% less tumor than the siQ control. MSN-siTWIST with cisplatin, without HA, provided similar results to our previous studies 32 , reducing tumor volume an additional 20% compared to cisplatin alone; whereas the MSN-HA-siTWIST with cisplatin chemotherapy treatment group (MSN-HA-siTWIST + cisplatin) exhibited the most promising outcome, with almost 90% decrease in tumor burden as compared to the siQ control and measured by bioluminescence (Figure 4).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…It has been reported that p65 increased the nuclear expression of Twist1 and interacted with Twist1 after TNF-α stimulation (Roberts et al, 2017;Yu et al, 2014). In addition, previous studies have pointed out that CypA interacts with p65 (Sun et al, 2014).…”
Section: Cypa Enhances Twist1-p65 Interaction and Nuclear Accumulationmentioning
confidence: 92%
“…It has been reported that Twist1 interacts with p65 to regulate TNF-α-mediated EMT (Li et al, 2012;Roberts et al, 2017;Yu et al, 2014). We performed co-immunoprecipitation assays to explore the effect of CypA on the interaction between Twist1 and p65.…”
Section: Cypa Enhances Twist1-p65 Interaction and Nuclear Accumulationmentioning
confidence: 99%